2020
DOI: 10.1371/journal.pone.0237917
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous evaluation of metabolomic and inflammatory biomarkers in children with different body mass index (BMI) and waist-to-height ratio (WHtR)

Abstract: Metabolic disturbances and systemic pro-inflammatory changes have been reported in children with obesity. However, it is unclear the time-sequence of metabolic or inflammatory modifications during children obesity evolution. Our study aimed to quantify simultaneously metabolomic and inflammatory biomarkers in serum from children with different levels of adiposity. For this purpose, a cross-sectional study was used to perform targeted metabolomics and inflammatory cytokines measurements. Serum samples from chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Despite, all included studies that reported on non-esterified fatty acids noted increased circulating values. This could result from their release by saturated adipocytes into the blood stream, leading to lipotoxicity, and in turn, interfering in a vicious way with insulin-responsive metabolic pathways (Chavira-Suárez et al 2020 ). This is, higher levels of non-esterified fatty acids have been reported to activate immune and oxidative stress pathways (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite, all included studies that reported on non-esterified fatty acids noted increased circulating values. This could result from their release by saturated adipocytes into the blood stream, leading to lipotoxicity, and in turn, interfering in a vicious way with insulin-responsive metabolic pathways (Chavira-Suárez et al 2020 ). This is, higher levels of non-esterified fatty acids have been reported to activate immune and oxidative stress pathways (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lipogenesis). This could be reflective of increased rates of lipogenesis and concordant overproduction of ROS, pro-inflammatory prostaglandins and adipokines and altered nitric oxide (Chavira-Suárez et al 2020 ), thereby inflecting immune response (Fig. 3 , 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both tyrosine and alanine were previously found as potential early markers for the onset of insulin resistance and were positively associated with adiposity in children of various ethnicities [19,20,22,23,40]. In fact, Hellmuth et al postulated that tyrosine elevations in obese children precede elevations in branched chain amino acids [41].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated pediatric metabolic disorders using metabolomics and have primarily focused on single risk factors, in particular obesity and insulin resistance [16][17][18][19][20]. Only three metabolomics studies derived an internal (study-specific) continuous MetS zscore, and all were conducted in adolescents and older children (10 years and up) [21][22][23].…”
Section: Introductionmentioning
confidence: 99%